Retracted: ZIC2 promotes viability and invasion of human osteosarcoma cells by suppressing SHIP2 expression and activating PI3K/AKT pathways. Issue 2 (18th October 2017) - Huang, Shuaihao; Jin, Anmin
Abstract: Osteosarcoma is a malignant tumor of the skeletal system. The zinc finger transcription factor ZIC2 has been reported to be highly expressed in human cancers. The present study evaluated the effects of ZIC2 and the possible underlying mechanisms in the human osteosarcoma cells. The expression levels of ZIC2 in human fetal osteoblastic cell line (hFOB1.19), osteosarcoma cell lines (U‐2OS, SaoS2, and MG63), normal bone tissue, and osteosarcoma tumor were analyzed by Western blot, and real‐time quantitative RT‐PCR (qRT‐PCR). Osteosarcoma cells with either overexpressed ZIC2 or suppressed ZIC2 were analyzed to determine cell viability, colony formation, and cell invasion. The expressions of SHIP2 and PI3K/AKT signal pathway‐related proteins were analyzed by Western blot and qRT‐PCR. We first showed that ZIC2 is highly expressed in osteosarcoma cells and tissues. Then we demonstrated that overexpression of ZIC2 promoted viability, migration, and invasion of osteosarcoma cells, whereas suppression of ZIC2 showed opposite effects. Furthermore, SHIP2 expression was negatively regulated by ZIC2. Importantly, ZIC2 overexpression activated the PI3K/AKT signal pathway; however, overexpressed SHIP2 inhibited these effects. Lastly, we showed that activation of the PI3K/AKT signal pathway is essential for the effects of ZIC2 on osteosarcoma cells, as the effects of ZIC2 on the osteosarcoma cells were reversed by a PI3K/AKT inhibitor. Overall, ZIC2 is highly expressed in osteosarcoma cells and tissues, and its overexpression promotes viability, invasion of osteosarcoma cells via SHIP2 suppression, and PI3K/AKT activation. Thus, ZIC2 can be considered as a novel drug target for osteosarcoma management. Abstract : ZIC2 is highly expressed in osteosarcoma cells and tissues. ZIC2 overexpression promotes viability, invasion, and metastasis of osteosarcoma cells. ZIC2 suppression inhibits viability, invasion, and metastasis of osteosarcoma cells. SHIP2 expression is negatively regulated by ZIC2. Activation of the PI3K/AKT signal pathway is essential for the effects of ZIC2 in osteosarcoma cells.